CONJUNCTIVE USE OF SPECTRAL GAMMA-RAY LOGS AND CLAY MINERALOGY IN DEFINING LATE JURASSIC-EARLY CRETACEOUS PALAEOCLIMATE CHANGE (DORSET, U.K.) - Schnyder J.; Baudin F.; Ruffell A.; Deconinck J.-F. (My University, 2006)
Detrital clay mineralogy is controlled by weathered source rock, climate, transport and deposition that in turn influence the spectral gamma-ray (SGR) response of resultant sediments. Whilst a palaeoclimate signal in clay mineralogy has been established in some ancient successions, the SGR response remains contentious, largely because the data sets have yet to be collected at the same or appropriate vertical scales to allow comparison. In addition, the influence of organic matter on SGR is not always considered. Here, we present clay mineralogical, total organic carbon (TOC) and SGR analyses from the late Jurassic and early Cretaceous of the Wessex Basin, a period of previously documented palaeoclimate change. The aim of this paper is to estimate the sensitivity of SGR as palaeoclimatic tool, SGR and clay mineral data having been collected at the same sample points, making this one of the most rigorous comparison of clay mineral and SGR to date. Overall, the correlation between high thorium/potassium or thorium/uranium and kaolinite associated with a well-established palaeoclimate change shows that elevated thorium may be used as a proxy for humid palaeoweathering, as suggested by few previous studies. © 2005 Elsevier B.V. All rights reserved.
Keywords: CLAY MINERALOGY; DORSET; JURASSIC-CRETACEOUS BOUNDARY; PALAEOCLIMATE; PURBECK FACIES; SPECTRAL GAMMA RAY; Cretaceous; Jurassic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская